Reconfiguring Religious Authority and Ethical Governance in Islamic Political Thought: A Comparative Literature Review - Fuadi, Azrian Isyfaul (Yayasan Sinergi Kawula Muda, 2024)
The Islamic political thought has long served as a foundational discourse for governance in Muslim-majority societies, continuously adapting to evolving historical, theological, and socio-political conditions. This narrative review investigates the development and transformation of Islamic political ideologies, from classical treatises to contemporary reformist and feminist interpretations. Utilizing a structured literature search through academic databases such as Scopus and Google Scholar, the review selected peer-reviewed sources focused on themes of Islamic governance, religious authority, gender justice, and regional variations. The findings reveal that classical texts such as the Siyasatnama and the Muqaddimah continue to inform present-day governance through concepts like justice and social solidarity. Shi'a political frameworks emphasize divine sovereignty through clerical authority, contrasting with more decentralized Sunni models. Reformist thinkers like Jamal al-Din al-Afghani and Fazlur Rahman advocate for contextual reinterpretation and democratic engagement. The influence of systemic factors—including colonial legacies, economic crises, and cultural diplomacy—demonstrates both the resilience and the adaptability of Islamic political thought. Feminist contributions and grassroots activism further enrich the discourse, emphasizing inclusivity and civic engagement. The review concludes that overcoming governance challenges and ideological rigidity requires educational reform, inclusive policy-making, and expanded theological dialogue. These steps are essential for ensuring that Islamic political thought remains relevant and impactful in contemporary governance. The study highlights the need for future research on digital political engagement and comparative models across global Muslim societies.